Quality of Care for Children with Severe Disease in the Democratic Republic of the Congo - Clarke-Deelder, Emma (Springer Nature, 2021)
Despite the almost universal adoption of Integrated Management of Childhood Illness (IMCI) guidelines for the diagnosis and treatment of sick children under the age of five in low- and middle-income countries, child mortality remains high in many settings. One possible explanation of the continued high mortality burden is lack of compliance with diagnostic and treatment protocols. We test this hypothesis in a sample of children with severe illness in the Democratic Republic of the Congo (DRC).